Reviewing Sanitation in Uganda to Reach Sustainable Development Goals - Gibson, Jim; Eales, Kathy; Nsubuga-Mugga, Chris (World Bank, Washington, DC, 2018)
This policy note draws upon information collated during a diagnostic study on the state of household and institutional sanitation in rural and urban areas, and presents the barriers and drivers of improvement of sanitation in the country. Low median household incomes, which constrain investment in sanitation improvement, are a major barrier to improvement of sanitation in the country; as well as chronic underfunding of local governments which severely limits their ability to drive sanitation improvement programs. Advancing sanitation improvement systematically and sustainably requires a fundamental shift from reliance on externally-funded project-based approaches, to a sustained focus on sanitation by local governments, with dedicated funding from central government to address their sanitation mandate on an ongoing basis. The current rate of progress in the sector reflects what can be achieved with the current quantum of funding. The sector is currently stuck in a low-level equilibrium, and prospects for achieving different sanitation outcomes with the same resources are limited. In addition, poor sanitation is compromising Uganda’s schools and education goals. Achieving safely managed sanitation across the entire service chain will require concerted effort on all fronts. The policy note makes recommendations and presents an action plan outline on key interventions that should form part of an ongoing program.